Sexting as Moral Panic: An Exploratory Study into the Media's Construction of Sexting - Marker, Brandon Scott (2011)
This paper presents a study of sexting as a socially constructed moral panic. Central to a social construction of moral panic perspective is the role the media plays in creating the panic. The purpose of this exploratory study was to make sense of the phenomenon of sexting by analyzing media reports for indication that sexting was constructed by the media as a moral panic. A content analysis was conducted on media reports for three concepts: Theme Setting, Sensational Stories, and Policy Changes. I conclude that sexting is constructed as a moral panic by the media